Reaktivasi Kelompok Perhutanan Sosial melalui Usaha Agroforestri di Desa Aniungan Kabupaten Balangan - Mustafa, Muhammad Khaidir; Khairussalam; Bakhsar, Intan Septiana; Inayah; Azizah, Aulia; Wilastri, Dian; Putri, Paradise Setya; Ansari, Mochammad Iqbal; Al Ausyad, Muhammad Adi Syahbana; Rahmah; Herliyani (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented in Aniungan Village, Halong Subdistrict, Balangan Regency. Aniungan Village, which is the customary territory of the Dayak Halong people in the Meratus mountain range, has forests that are managed based on a zoning system and strong local wisdom norms. However, village forest management faces significant challenges in the form of stagnation and low institutional capacity of the Village Forest Management Institution (LPHD). The inactivity of this formal institution risks weakening community control and causing uncontrolled forest degradation. This community service program was implemented as a solution to revitalize the LPHD's function so that it can play a dual role in preserving the environment and improving community welfare, based on the principles of being active, participatory, and sustainable. The main methods used were the Participatory Approach and the live-in method, which served to build active collaboration and foster a sense of community ownership of the program. The solutions implemented included institutional strengthening through counseling and the provision of capital stimulus in the form of 1,000 productive tree seedlings. The summary of the results shows that the program successfully carried out comprehensive counseling on LPHD governance and Nusantara Agroforestry techniques. The program also distributed a total of 1,000 seedlings (Mahogany, Jengkol, Petai, Soursop, Avocado, Durian) to 51 recipients, followed by planting activities on community land. The main results of this intervention were an increase in collective knowledge and the re-creation of a spirit of solidarity among LPHD members and the community, which became the initial foundation for realizing organized land management. This community service concluded that the reactivation of the LPHD institution, synergized with local wisdom and the adoption of the agroforestry model, is a key strategy for achieving the sustainability of the Aniungan Village Forest.